2021
DOI: 10.1186/s12893-020-01027-9
|View full text |Cite
|
Sign up to set email alerts
|

Placenta previa with posterior extrauterine adhesion: clinical features and management practice

Abstract: Background A diagnostic sign on magnetic resonance imaging, suggestive of posterior extrauterine adhesion (PEUA), was identified in patients with placenta previa. However, the clinical features or surgical outcomes of patients with placenta previa and PEUA are unclear. Our study aimed to investigate the clinical characteristics of placenta previa with PEUA and determine whether an altered management strategy improved surgical outcomes. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In this systematic literature search, we identified one study that reported the surgical morbidity of PP patients with endometriosis [ 56 ]. This study included 24 women with PP who had posterior extrauterine adhesion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this systematic literature search, we identified one study that reported the surgical morbidity of PP patients with endometriosis [ 56 ]. This study included 24 women with PP who had posterior extrauterine adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…This retrospective study also examined the characteristics of PP complicated with endometriosis and found that endometriosis was correlated with a higher rate of total PP (66.7% vs. 42.7%, p = 0.04), posterior placenta (95.8% versus 63.2%, p < 0.01), longer cervical length (56.1 mm versus 36.1 mm, p < 0.01), and increased intraoperative bleeding (1.515 mL versus 870 mL, p < 0.01) compared to those without endometriosis [ 56 ]. These findings suggest that PP complicated with endometriosis appears to be a high risk factor for postpartum hemorrhage; however, the underlying cause of increased intraoperative bleeding remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations